First report of totally robotically assisted hybrid coronary artery revascularization combining RE‐MIDCAB and R‐PCI: Case report. Issue 9 (11th June 2022) - Bertolone, Dario T.; Bermpeis, Konstantinos; Gallinoro, Emanuele; Esposito, Giuseppe; Paolisso, Pasquale; De Colle, Cristina; Sonck, Jeroen; Collet, Carlos; De Bruyne, Bernard; Barbato, Emanuele; Van Praet, Frank; Wyffels, Eric
Abstract: A 62‐year‐old man presents to the Cardiology Department with a history of angina on exertion. Invasive coronary angiography revealed a severe three vessels coronary artery disease. The "Hybrid Heart Team" successfully performed a fully robotically assisted hybrid revascularization combining robotically enhanced‐minimally invasive direct coronary artery bypass on the left anterior descending (LAD) and robotically assisted percutaneous coronary intervention on non‐LAD lesions.